Caracterização das demandas físicas e fisiológicas associadas à partida de tênis - de Melo dos Santos, M.; Vitasovic Gomes, R.; Moreira, A.; Calve, T.; Cayioa Santos, R.; Dario Capitani, C.; Saldanha Aoki, M. (Brazilian Journal of Biomotricity, 2012)
The aims of this study were: a) describe the physical demands of a Tennis match and B) determine the internal load responses during a tennis match. Twelve young tennis players (18 ± 0.8 years, 1.76 ± 3.4 m and 68 ± 2.3 kg) ranked in Brazilian Tennis Confederation participated in the present study. The external loads parameters (real playing time, length of games, length of points and number of strokes per point) were analyzedduring a match lasting 180 minutes. Furthermore, the heart rate (HR) profile and the rating of perceived exertion (RPE) were determined during the match. Most points (72%) was determined in the range of one to two strokes and a large portion of scores (54.6%) was decided in less than 6 seconds. Regarding the analysis of the distribution of time spent in a given HR zone, it was observed an increase in the percentage of time in the high intensity zone, 25.1% in the first hour, 28.3% in the second hour and 32.0% in the third hour, respectively. The RPE also increased gradually during the match, 3.3±1.4 in the first hour, 4.4±1.2 in the second hour and 5.8±1.5 in the third hour. The analysis of the external load parameters (duration and number of strokes) suggests that these demands influence the internal responses (HR and RPE). The intermittent nature of the tennis match determines the diverse HR distribution between the intensity zones. The reduction of the length of points / number of strokes recorded on the final stages of the match is accompanied by increased RPE and the time spent in the high intensity HR zone.